Da’wah as Moral Presence: Reframing Multicultural Da‘wah through the Ethics of ‘Ibad Al-Rahman - Sumadi Sumadi (al-Afkar, Journal For Islamic Studies, 2026)
In Muslim-majority yet religiously plural societies, da‘wah increasingly unfolds within multicultural and digitally mediated public arenas where its social and ethical consequences are closely scrutinized. Although recent scholarship on digital da‘wah has generated important insights into media adaptation and audience engagement, it often conceptualizes da‘wah instrumentally, prioritizing visibility and communicative efficacy over ethical formation. This article reframes da‘wah as moral presence, understood as ethics-centered communication grounded in embodied character, relational restraint, and public responsibility. Employing the Qur’anic moral figure of ʿIbad al-Rahman as a conceptual lens, the study develops a normative framework that foregrounds ethical subjectivity as integral to communicative effectiveness in plural contexts. Rather than offering textual exegesis, the article synthesizes empirical findings on digitally mediated preaching, intercultural sensitivity, and religious personality with normative discourses on harmony and moderation. It argues that da‘wah attains public legitimacy not through persuasion alone, but through the moral comportment of the da‘i as a public ethical actor.